Analisis Nilai-Nilai Pada Budaya dan Seni di Indonesia : Studi Kasus Tari Jaipong dalam Perspektif Pendidikan Agama Islam - Nur Khalishah; Pipit Puji Astuti; Reza Maulana; Zakiyahtuz Zahra; Ade Hidayat (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to examine in-depth the cultural, social, and religious values ​​embodied in the traditional Jaipong dance and their relevance to cultural development in Islamic Religious Education (PAI). The approach used was a qualitative study based on literature review with an ethnopedagogical perspective, which views local culture as a source of learning. The results indicate that Jaipong Dance not only possesses aesthetic elements as part of artistic expression, but also contains moral, social, and spiritual values ​​that reflect the character of the Sundanese people. These values ​​include discipline, creativity, cooperation, courtesy, self-confidence, and a spirit of togetherness and nationalism. All of these values ​​align with the principles of Islamic education, which emphasize noble morals, respect for culture, and the development of student character. Therefore, the integration of local arts and culture, such as Jaipong, into Islamic Religious Education (PAI) learning, can enrich educational methods, provide contextual learning, and foster students' love for Islamic values ​​that are more humanistic, inclusive, and applicable in everyday life.